GG-03 IRF5 genetic risk variants drive an SLE immune-phenotype in healthy donors. (August 2018) - Li, Dan; Matta, Bharati; Song, Su; Simpfendorfer, Kim; Gregersen, Peter; Barnes, Betsy J
Abstract : Background: Gene expression profiling has provided significant insight into SLE pathology through the identification of an IFN gene signature, a neutrophil-specific signature, and a plasma cell signature that correlate with disease activity. While genetic variants have also been shown to correlate with disease activity, the mechanism(s) by which they confer risk to SLE are not fully elucidated. Genetic variants within or near the interferon regulatory factor 5 ( IRF5 ) locus associate with SLE across ancestral groups. Four IRF5 variants have been identified that strongly associate with SLE risk and make up the major risk haplotype in European Caucasians (rs2004640, rs10954213, rs10488631, and rs142738614 (CGGGG indel)). To determine how these variants contribute to SLE risk, we performed global immune-phenotyping on healthy donors homozygous for the major risk and non-risk haplotypes. Methods: Healthy donors (no personal/family history of autoimmune/inflammatory diseases or cancer) are participants of the Feinstein Genotype and Phenotype (GaP) Registry that is genotyped on the Illumina Human Immunochip. Individual donors carrying the homozygous risk and non-risk haplotype were called in a minimum of 4 times over a 2 year-period for independent blood draws. Lymphoid and myeloid subsets were analyzed by flow cytometry on a BD Fortessa. Serum autoantibodies were measured by ANA-Hep-2, ELISA and a multiplex antibody profiling array. IRF5 expression and activation were determined on an Amnis Imagestream X Mark II imaging flow cytometer. B cell differentiation was determined by in vitro culture. NETosis was determined by fluorescent microscopy and flow cytometry. Ex vivo co-culture was used to identify antigenic triggers in risk and non-risk donors that drive B cell differentiation. Results: We observed a striking homogeneity within haplotype groups that was conserved over time and could be replicated by ex vivo co-culture. We found that the IRF5 risk haplotype confers cell lineage-specific changes that mimic pre-symptomatic SLE. Interestingly, and contrary to what has been previously reported in B lymphoblastoid cell lines and SLE immune cells, IRF5 genetic variants had no effect on the overall levels of IRF5 expression in cells from healthy donors. Instead, IRF5 risk carriers had elevated numbers of circulating plasmacytoid dendritic cells and plasma cells, positive ANA, constitutive IRF5 hyper-activation, and spontaneous NETosis. Conclusions: Data suggest that individuals carrying IRF5 -SLE risk haplotypes are particularly susceptible to environmental or stochastic influences that can trigger a transition to chronic immune activation, which in turn predisposes to the development of clinical lupus.